Metformin reduces c-Fos and ATF3 expression in the dorsal root ganglia and protects against oxaliplatin-induced peripheral sensory neuropathy in mice. (14th September 2019) - Pereira, Anamaria Falcão; Pereira, Lus Mário Silva; Silva, Cristiane Maria Pereira; Freitas Alves, Bruno Wesley; Barbosa, Jéssica Sales; Pinto, Francisco Maxwell Martins; Pereira, Ana Carolina; Silva, Karla Oliveira; Pontes, Renata Bessa; Alencar, Nylane Maria Nunes; Lima-Júnior, Roberto César Pereira; Vale, Mariana Lima
Highlights: Metformin protects against oxaliplatin-induced peripheral sensory neuropathy. Metformin reduces the expression of c-Fos and ATF3 in the dorsal root ganglia. Metformin prevents oxaliplatin-induced neuronal injury and hyperactivation. Abstract: Oxaliplatin is a third-generation platinum drug commonly used as the first line treatment of metastatic colorectal cancer. Oxaliplatin-based anticancer regimens course with dose-limiting neurotoxicity. The pharmacological strategies used to manage such side effect are not totally effective. Metformin is an anti-diabetic drug that is described to negatively modulate painful diabetic neuropathy. Then, this study aimed to assess the effect of metformin in the oxaliplatin-induced peripheral sensory neuropathy in mice. For that purpose, Swiss male mice were injected with oxaliplatin (1, 2 or 4 mg/kg, i.v., twice a week with a total of nine injections) alone or in combination with daily administration of metformin (250 mg/kg, p.o.). Thermal and mechanical nociceptive tests were performed once a week for five weeks. Then, the animals were euthanized on day 35 post-first injection of oxaliplatin and the dorsal root ganglia were harvested for the assessment of c-Fos and ATF3 expressions. Oxaliplatin caused a nociceptive response accompanied by the increased expression of c-Fos and ATF3 in the dorsal root ganglia and spinal cord. In addition, the oxaliplatin-associated nociception was significantly attenuated by metformin ( P  < 0.05), which also reduced the expression of c-Fos and ATF3 ( P  < 0.05). Therefore, metformin protected from the peripheral sensory neuropathy induced by oxaliplatin, which was confirmed by the reduction of c-Fos and ATF3 expression, two known neuronal activation and damage markers, respectively.